A new approach in identifying and evaluating quality risks in the pharmaceutical industry - Mohammad Hajimolaali; Abbas Kebriaeezadeh; Akbar Abdollahiasl; Hossein Safari; Alireza Yektadoost (Tehran University of Medical Sciences, 2018)
Background: Failure Mode and Effects Analysis (FMEA) is a highly structured and systematic technique for risk analysis, commonly used in all procedures of the pharmaceutical industry, from the design of the production facility and new product development to the product release. The important part of this method is the identification of risks and determining the risk priorities. Methods: This study has been carried out in two steps: in the first step, all possible quality related risks have identified through literature review and interviews with experts of the pharmaceutical industry, subsequently these experts validated recognized risks. In the next step, the valid risks analyzed and evaluated through the combination of FMEA and Fuzzy TOPSIS methods. Results: More than 100 main quality risks were identified in the pharmaceutical manufacturing companies. These risks originate from the redundant practices and processes of the industry. Consequently, twenty of the identified risks recognized as effective risks in the industry. Human errors in production, inadequate supervision on conduction of qualification of the production machineries, improper qualification in design and implementation of the heating, ventilation, and air-conditioning (HVAC) system, lack of standard procedures for handling of the non-conforming products, inadequate supervision on conduction of cleaning validation of the production facilities, and weakness in the documentation have been recognized as the most important risks in this study. Conclusion: Risks survey results can point to the prominence of the quality assurance unit and its vital but partially neglected role in the generic pharmaceutical industry.